(untitled) (Architecture Image Studies, 2025)
Construction site accidents in Korea can result in work stoppages, which in turn lead to claims and adversely affect project progress. Although the number of fatal accidents has decreased in recent years, the construction industry still records more than twice as many fatalities compared to other industries. One contributing factor to this is the increasing number of foreign workers. Due to language barriers, lack of knowledge and experience, and cultural differences, foreign workers are more susceptible to frequent accidents. Therefore, this study seeks to investigate and analyze the current state of safety management for foreign workers at construction sites. Through this research, it will be possible to review the direction of safety education programs targeting foreign workers. Furthermore, the findings are expected to facilitate the assessment and improvement of safety management practices not only for foreign workers but also for domestic workers.